EKSTRAKSI RUANG FASE KLASIK DARI GRUP LIE SIMETRI - , CAHAYA ROSYIDAN; , Dr. rer. nat. Muhammad Farchani Rosyid, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
We have done research in the object of geometry symplectic. That is finding a classical phase space of symmetry Lie group. The symmetry Lie group that been considered is SU(2)U(1). We obtain the classical phase space of the SU(2)U(1) is a manifold symplectic (SU(2)U(1)=G